44‐1: Distinguished Paper: Electrophoretic Display Comprising Black, White, Red, and Yellow Particles. Issue 1 (28th June 2022) - Zang, HongMei; Lin, Craig; Du, Hui; Gu, Haiyan; Parent, Mary; Chen, Yajuan; Liu, Lei
Abstract : Following the commercial success of the three‐particle electrophoretic display E Ink Spectra 3000, a four‐particle electrophoretic display, Spectra 3100, was developed and launched as a premier product in 2021. It targets electronic shelf label applications and signage applications by providing vibrant optical states of black, white, red, yellow and dithering capability. Specially engineered black, white, red and yellow particles in the electrophoretic ink respond to different electric fields to show their intrinsic colors on the display. For the best readability under various light conditions, angles and distances, Spectra 3100 imaging film can reach a typical contrast ratio of 30 while maintaining a maximum driving voltage of 15V. The ink is coated and sealed in a thin film Microcup structure using an additive and high yield roll‐to‐roll process.